Assessment of ultimate bearing capacity based on the hoek-brown failure criterion - Lai, G.T. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The ultimate bearing capacity is an essential requirement in design quantification for shallow foundations especially for structures built on large rock masses. In many engineering projects, structures built on foundation of heavily jointed rock masses may face issues such as instability and sudden catastrophic rock slope failure. Determination of the ultimate bearing capacity (Qult) of foundations resting on rock mass has traditionally been determined by employing several strength criterions. One of the accepted and widely implemented methods is to use the Hoek-Brown failure criterion 2002, where the required parameters are determined from a rock mass classification system, Geological Strength Index (GSI). This paper defines an assessment for ultimate bearing capacity (Qult) based on the Hoek-Brown failure criterion 2002 for a granitic rock slope beneath a 20 m diameter concrete water tank at Bandar Mahkota Cheras, Kajang, Selangor. Based on the Hoek-Brown failure criterion 2002, the ultimate bearing capacity (Qult) of rock mass was 7.91 MPa. The actual stress acting on the rock mass was 0.32 MPa. The assessment showed that the rock mass is safe since the ultimate bearing capacity (Qult) is 24.7 times higher than the actual stress acting on the rock mass.